O hiperpresidencialismo brasileiro: uma terceira onda de autocratização do regime democrático? - Rodrigues, Lucas Mateus Canabarro (2020)
The present work has as research theme the Brazilian hyperpresidentialism and a possible third wave of self-democratization of the democratic regime from the rise to power of President Jair Messias Bolsonaro, showing himself to be a potential autocrat since the election campaign. For the purposes of structuring this research, it was decided to divide the theme into two major chapters: 2. A DEMOCRACY CONCEPT: from democratization to the third wave of self-democratization of regimes and 3. A NEW FORM OF COMMUNICATION BETWEEN REPRESENTATIVES AND REPRESENTED: the election from Jair Bolsonaro to the Presidency of Brazil and the risk of fake news. In the first large chapter, it was decided to subdivide into 3 points: 2.1 in which some reflections on the concept of democracy and the phenomenon were addressed, 2.2 which alluded to the meaning of power within a democratic society and adoption presidentialism in CRFB / 88 and in 2.3 sought to describe the waves of democratization and self-democratization in different countries around the world. In the second great chapter it was also subdivided into 3 sub-chapters, and in sub-chapter 3.1 the concept of network society was approached from Manuel Castells, especially under the bias of the risks and opportunities for democracy from the internet. Subchapter 3.2 referred to the elections for the Presidency of the Republic of Brazil in 2018 and the challenges that the spread of fake news posed to the electoral election, leading to an extreme political polarization in social networks and society in general. Finally, in sub-chapter 3.3, we sought to face a possible third wave of selfdemocratization of the democratic regime with the arrival of Jair Messias Bolsonaro in power, an analysis carried out from a world context of the rise of autocratic leaders to power. The present work has as a research problem: the extent to which Brazilian hyperpresidentialism has been damaging the democratic attributes of Brazil and this may represent a third wave of self-democratization in progress. For that, it was used the method of dialectical approach, the method of historical procedure and the technique of bibliographic research, which proved to be the most adequate for the analysis of the proposed theme. In addition, this work is in perfect harmony with the area of concentration emerging rights in the global society, specifically rights in the network society, that is, one of the lines of research of the PPGD / UFSM.